Análise da vazão do IEEE 802.11 DCF em condições de tráfego insaturado em canais com desvanecimento η - μ - Silva, Heber Rabelo da (2016)
This dissertation investigates the performance, in terms of throughput, of the IEEE 802.11 DCF (Distributed Coordination Function) protocol. Applied to the Medium Access Control (MAC) sublayer, the model assumes unsaturated traffic conditions, propagation channel-induced error and capture effect of the desired signal in the presence of interfering signals in fading environment. The cochannel interference assumes an incoherent addition of the interfering signals. The main contribution of this work is to model the fading propagation channel through of the distribution η - μ which is a general fading distribution..Due to the flexibility of this distribution, it allows obtaining traditional distributions and it provides adjustable parameters to represent a more accurate propagation model for real environments. The numerical results presented provide important information for the performance analysis of IEEE 802.11 DCF protocol, and to better describe the channel behavior, results are shown in various scenarios. The results show the versatility of the displayed channel model and set the parameter μ as responsible for the coarse adjustment of the channel, while the parameter η defines the fine adjustment. The adjustment flexibility provided by the proposed channel model allows, by adjusting the parameters η and μ, the obtainment of traditional models Nakagami-m, Rayleigh and Hoyt as special cases.